1977
DOI: 10.1007/bf00446650
|View full text |Cite
|
Sign up to set email alerts
|

Energy conservation during aerobic growth in Paracoccus denitrificans

Abstract: Paracoccus denitrificans was aerobically grown in chemostat culture with succinate or gluconate as carbon source. Due to the presence of two phosphorylation sites in the respiratory chain and the absence of branching, theoretical P/O ratios of 1.71 and 1.82 were calculated for cells growing respectively with succinate and gluconate as carbon source. Using these data, 95% confidence intervals for the P/O ratio were determined, via a mathematical model, at 0.91-1.15 and 1.00-1.37 for sulphate-limited cultures, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…A number of possibilities to allow the determination of YA MAx and the P/O ratio from aerobic yield studies have been outlined by Stouthamer (1977). In heterotrophic cells the absence of phosphorylation site III has been demonstrated (Imai, Asano and Sato, 1967;Knobloch, Ishaque and Aleem, 1971 ;van Verseveld and Stouthamer, 1976;Meijer et al, 1977).…”
Section: Calculationsmentioning
confidence: 94%
See 1 more Smart Citation
“…A number of possibilities to allow the determination of YA MAx and the P/O ratio from aerobic yield studies have been outlined by Stouthamer (1977). In heterotrophic cells the absence of phosphorylation site III has been demonstrated (Imai, Asano and Sato, 1967;Knobloch, Ishaque and Aleem, 1971 ;van Verseveld and Stouthamer, 1976;Meijer et al, 1977).…”
Section: Calculationsmentioning
confidence: 94%
“…The calculations have been performed with the theoretical value for YATP (15.4) for growth with succinate and ammonia (Stouthamer, 1973) and for an experimental value (YmP = 7.5) determined for P. denitrificans ; van Verseveld, Meijer and Stouthamer, 1977). The YmP values for growth with nitrate and nitrogen with various ATP/N/ratios were calculated as described earlier for growth with glucose ( Table 1).…”
Section: Calculationsmentioning
confidence: 99%
“…However, in experiments of very similar design, using rotenone instead of piericidin A to inhibit electron flow in the site 1 region, Meijer et a&. (7) observed an t H + :O ratio of 3.0 associated with succinate oxidation. The cells in these separate investigations were grown under almost identical conditions in continuous culture, and it is, therefore.…”
Section: Reagentsmentioning
confidence: 95%
“…Hence, Meijer ef ak. (7) assumed that the cells in their experiments, which were grown aerobically in a chemostat under conditions of succinate limitation, were deficient with respect to coupling site 3 and concluded that the t H + :site ratio was equal to the stoichiometry of proton translocation associated with succinate oxidation ( tH+:site = t H + : 8 ratio = 3-4) in rotenonetreated cells. It would appear that one possible emplanation for the discrepancy between the results reported both in this paper and previously (6) and those of Meijer et at.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation